2012
DOI: 10.1111/j.1600-0854.2012.01398.x
|View full text |Cite
|
Sign up to set email alerts
|

The Host Endocytic Pathway is Essential for Plasmodium berghei Late Liver Stage Development

Abstract: The obligate intracellular liver stage of the Plasmodium parasite represents a bottleneck in the parasite life cycle and remains a promising target for therapeutic intervention. During this stage, parasites undergo dramatic morphological changes and achieve one of the fastest replication rates among eukaryotic species. Nevertheless, relatively little is known about the parasite interactions with the host hepatocyte. Using immunofluorescence, live cell imaging and electron microscopy, we show that Plasmodium be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
74
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(85 citation statements)
references
References 22 publications
9
74
1
Order By: Relevance
“…It is not known why the PV of successfully developing parasites does not acidify, despite fusion of the PVM with lysosomes, as shown in this and a previous study. 20 One possibility is that the PVM contains outward-directed proton pumps. However, this may not be necessary considering that the PVM contains pores for the easy uptake of nutrients of up to 855 Da, 39 and that proton gradients may not be able to form in such an environment because they need tight membranes without pores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not known why the PV of successfully developing parasites does not acidify, despite fusion of the PVM with lysosomes, as shown in this and a previous study. 20 One possibility is that the PVM contains outward-directed proton pumps. However, this may not be necessary considering that the PVM contains pores for the easy uptake of nutrients of up to 855 Da, 39 and that proton gradients may not be able to form in such an environment because they need tight membranes without pores.…”
Section: Discussionmentioning
confidence: 99%
“…19 One study suggested that lysosomes fuse with the PVM in P. berghei-infected hepatocytes. 20 We therefore sought to determine i) the dynamics of lysosome fusion in relation to LC3 recruitment to the PVM in infected cells, ii) whether the pH drops in the PV, and iii) whether the lysosomal protease CTSD (cathepsin D) is recruited to the PV.…”
Section: Lysosomes Are Attracted By Early-stage and Arrested Parasitesmentioning
confidence: 99%
“…A total of 50,000 and 25,000 Huh7 cells grown on coverslips or eight-well Lab-Tek chamber slides (Nunc), respectively, were seeded 1 d before infection with 10,000 Pb sporozoites and fixed at the indicated time points (10,15,18,21,24, and 48 hpi) after sporozoite addition. Cells grown on coverslips were fixed with 4% (vol/vol) paraformaldehyde for 15 min, washed three times with PBS, permeabilized in 0.2% (vol/vol) saponin or Triton in PBS for 20 min, blocked for 1 h with 0.1% (vol/vol) Triton in 1% (wt/vol) BSA in PBS, and incubated with the appropriate primary antibodies in blocking buffer for 1 h at room temperature or overnight at 4°C.…”
Section: Cell Biology Pnas Plusmentioning
confidence: 99%
“…However, little is known about intrahepatic Plasmodium stages with regard to interactions between the parasite and the host hepatocyte and their potential for nutrient uptake and/or exchange. Small molecules (up to 800 Da) can cross the PVM freely via specialized transport channels (14), whereas larger molecules might reach the parasite via association and possibly fusion of late endosomes, lysosomes, or amphisomes with the PVM (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Recently, Lopes da Silva et al [56] used bovine serum albumin (BSA) linked to 10 nm AuNP in order to follow their position in the parasite-host cell system, in the liver stage, a crucial phase of the Plasmodium development. The authors showed that when BSA-Au are loaded into the host cell endocytic pathway, the AuNP are later found within the parasite cytoplasm, showing the transport of materials from the host endocytic pathway towards the parasite interior, revealing a possible form of the parasite to obtain nutrients.…”
Section: Microscopy Assays Using Nanogoldmentioning
confidence: 99%